1998
DOI: 10.1530/eje.0.1380567
|View full text |Cite
|
Sign up to set email alerts
|

Intra-adrenal factors are not involved in the differential control of cortisol and adrenal androgens in human adrenals

Abstract: The differential control of adrenal androgens and cortisol may be due to intra-adrenal factors, which may be age-or sex-related, or due to extra-adrenal factors, such as circulating hormones. The purpose of this study was to identify any intrinsic differences that may exist in steroidogenic production occurring within adrenals obtained from males and females, and any maturational differences that may evolve with age. Using human adrenals from 48 transplant donors (32 males, 16 females; ages 5-60 years), the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…However, in humans the male and female ZR are similar in both size and cytochrome b5 expression (27). Also, cultured male and female adrenal glands respond with identical levels of DHEA secretion when stimulated by ACTH (2). Further, females receiving long-term treatment with T show an increased response of DHEA to ACTH stimulation as compared to female controls (28, 29), suggesting that the adrenal machinery is the same in males and females, but the hormonal input from the HPG axis can modulate adrenal output.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in humans the male and female ZR are similar in both size and cytochrome b5 expression (27). Also, cultured male and female adrenal glands respond with identical levels of DHEA secretion when stimulated by ACTH (2). Further, females receiving long-term treatment with T show an increased response of DHEA to ACTH stimulation as compared to female controls (28, 29), suggesting that the adrenal machinery is the same in males and females, but the hormonal input from the HPG axis can modulate adrenal output.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear, however, that the gross, cellular, and molecular adrenal structure of males and females is essentially similar, suggesting that some factor outside the adrenal gland is responsible for the greater secretion of DHEA/S in males (2). Given that the sex differences in DHEA/S are most pronounced during early adulthood, it is plausible that the different levels of sex-steroid hormones between adult males and females may play a contributing role.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, over 45 steroids including androgens have been isolated and chemically characterized from adrenal gland extracts, and studied on the function (Norman and Litwack, 1997). Recently, Fearon et al (1998) reported that the differential control of adrenal androgens and cortisol in human. Thus, the existence of interrenal androgen may be needed to consider on the relationship between the function of HIP axis and stress in teleost.…”
Section: Discussionmentioning
confidence: 99%
“…Extraadrenal factors (such as prolactin, growth hormone, insulin, cytokines, sex steroids and pituitary POMC-derived peptides, such as b-endorphin and joining peptide) may also explain the variation in production of cortisol and androgens by controlling adrenal androgen biosynthesis and secretion. Recently, it was shown that adrenal androgen production does not correlate with age and sex, suggesting that extraadrenal rather than intraadrenal factors may modulate cortisol and androgen production [16].…”
Section: Introductionmentioning
confidence: 99%